The Nsp12-coding region of type 2 PRRSV is required for viral subgenomic mRNA synthesis. Issue 1 (1st January 2019) - Wang, Tong-Yun; Fang, Qiong-Qiong; Cong, Feng; Liu, Yong-Gang; Wang, Hai-Ming; Zhang, Hong-Liang; Tian, Zhi-Jun; Tang, Yan-Dong; Cai, Xue-Hui
ABSTRACT: As one of many nonstructural proteins of porcine reproductive and respiratory syndrome virus (PRRSV), nonstructural protein 12 (Nsp12) has received relatively little attention, and its role in virus replication, if any, is essentially unknown. By the application of reverse genetic manipulation of an infectious PRRSV clone, the current study is the first to demonstrate that Nsp12 is a key component of PRRSV replication. In addition, the biochemical properties of Nsp12 were evaluated, revealing that Nsp12 forms dimers when exposed to oxidative conditions. Furthermore, we systemically analyzed the function of Nsp12 in PRRSV RNA synthesis using a strand-specific PCR method. To our surprise, Nsp12 was not found to be involved in minus-strand genomic RNA (-gRNA) synthesis; importantly, our results indicate that Nsp12 is involved in the synthesis of both plus- and minus-strand subgenomic mRNAs (+sgmRNA and -sgmRNA). Finally, we found that the combination of cysteine 35 and cysteine 79 in Nsp12 is required for sgmRNA synthesis. To our knowledge, we are the first to report the biological role of Nsp12 in the PRRSV lifecycle, and we conclude that Nsp12 is involved in the synthesis of both + sgRNA and -sgRNA.